The Implementation Of The Employment Agreement For Indonesian Migrant Workers In Saudi Arabia - Wafda Vivid Izziyana; Harun Harun; Absori Absori; Kelik Wardiono; Arief Budiono (Sociological Jurisprudence Journal, 2019)
The placement program of Indonesian migrant workers overseas is the Indonesian government’s program for the society’s welfare. One of the referential laws used in the working relations between the Indonesian migrant workers and the Arabic employers is the employment agreement. The Saudi Arabian employment agreement implements the sharia law which is influenced by the Hambali school of taught. The King’s decree No. M/51 year 2005 regulates the labor laws in Saudi Arabia, and this country’s government only accepts employment agreements written in Arabic. The solution is that the employment agreements written in two languages are prepared, with Arabic as the authoritative language. Apart from implementing the Kafala System, as a substitute of tax, Saudi Arabia also implements the Nitaqat Policy. The employment agreements in Saudi Arabia have a high risk of being misused by the agencies, as the position of the Indonesian migrant workers is under the responsibility and under the power of the agencies, who have the right to terminate or to send the workers back home if there are some problems. The employment agreements are made because of the employer’s complaints on how the migrant workers often run away, which undoubtedly causes them a high loss. The aim of the contract is so that both parties may achieve a win-win solution, and that they are both given protection. Yet, the contract also limits the participation of the host country’s delegates, as all affairs are given to the Saudi Arabian Immigration Office. The employment agreement must be owned by both parties. Yet, based on some researches established by the Embassy of the Republic of Indonesia’s safe house, it is known that almost none of the migrant workers keep an employment agreement. Another problem is that there are multiple contracts: one before departing for Saudi Arabia, and a different one after having arrived in the country. Another written agreement that is signed by the employer and the agency in Saudi Arabia doesn’t involve the domestic worker. The three contracts which are signed in Indonesia, in front of the Immigration Office, and the one-sided contract between the employer and the agency regulates the same thing, though there is a chance that in all three contracts, the wages written are different.